Costimulation of IL-2 production through CD28 is dependent on the size of its ligand. - Lim, H; Cordoba, S; Dushek, O; Goyette, J; Taylor, A; Rudd, C; van der Merwe, P (American Association of Immunology, 2015)
Optimal T cell activation typically requires engagement of both the TCR and costimulatory receptors, such as CD28. Engagement of CD28 leads to tyrosine phosphorylation of its cytoplasmic region and recruitment of cytoplasmic signaling proteins. Although the exact mechanism of CD28 signal transduction is unknown, CD28 triggering has similarities to the TCR, which was proposed to use the kinetic-segregation (KS) mechanism. The KS model postulates that, when small receptors engage their ligands within areas of close (∼15 nm) contact in the T cell/APC interface, this facilitates phosphorylation by segregating the engaged receptor/ligand complex from receptor protein tyrosine phosphatases with large ectodomains, such as CD45. To test this hypothesis, we examined the effect of elongating the extracellular region of the CD28 ligand, CD80, on its ability to costimulate IL-2 production by primary T cells. CD80 elongation reduced its costimulatory effect without abrogating CD28 binding. Confocal microscopy revealed that elongated CD80 molecules were less well segregated from CD45 at the T cell/APC interface. T cells expressing CD28 harboring a key tyrosine-170 mutation were less sensitive to CD80 elongation. In summary, the effectiveness of CD28 costimulation is inversely proportional to the dimensions of the CD28-CD80 complex. Small CD28-CD80 complex dimensions are required for optimal costimulation by segregation from large inhibitory tyrosine phosphatases. These results demonstrate the importance of ligand dimensions for optimal costimulation of IL-2 production by T cells and suggest that the KS mechanism contributes to CD28 signaling.